Compliance with Recommendations on Work Schedule for Shift Nurses in South Korea - Jiyeon Lee; Ihn Sook Jeong (Elsevier, 2021)
Background: A well-designed shift schedule has been reported to have a positive effect on improving health problems associated with shift work. This study aimed to identify compliance with the 17 recommendations on work schedule (WSRs) for shift nurses and related factors. Methods: The descriptive study was conducted with 182 nurses who worked in three shifts for more than 1 year at superior general and general hospitals in three regions. Data were collected with self-administered questionnaire and 13-week work schedule tables, and analyzed with both person- and cycle-based compliance. Results: Person-based compliance was 11.77 among 17 items in total. However, no one completely complied with WSRs of "no work on weekends" and which showed the lowest cycle-based compliance (22.3%). Compliance with some WSRs was related to hospital type, proportion of nurses in school and having standards on work schedule at institutional level. Conclusion: Compliance with WSRs of shift nurses in Korea is still unsatisfactory, and one day off after night shift and work on weekend are quite common. Hospitals should keep the standards on work schedule, monitor compliance with standards, and try to introduce modified shift systems to improve the current problems.